2003
DOI: 10.1373/49.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Total Iron-binding Capacity Calculated from Serum Transferrin Concentration or Serum Iron Concentration and Unsaturated Iron-binding Capacity

Abstract: able in borderline cases. The routine use of other biomarker assays, such as HFABP in conjunction with tGST activity, could provide complementary information on the potential allograft "viability". This is illustrated by the fact that there was better segregation of donor categories (controlled vs uncontrolled) with HFABP than with tGST activity. This finding therefore warrants continued evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 11 publications
4
52
0
Order By: Relevance
“…Although some articles suggest that the relation between transferrin and TIBC is not fixed, others found that when each test is measured precisely and without bias, the ratio of TIBC (in mol/l) to transferrin (in g/l) is indeed close to the expected value of 25.0 [25,26] . Also, recent studies found high significant correlations between the TIBC and the serum transferrin values, even without this proposed calibration [27] .…”
Section: Discussionmentioning
confidence: 96%
“…Although some articles suggest that the relation between transferrin and TIBC is not fixed, others found that when each test is measured precisely and without bias, the ratio of TIBC (in mol/l) to transferrin (in g/l) is indeed close to the expected value of 25.0 [25,26] . Also, recent studies found high significant correlations between the TIBC and the serum transferrin values, even without this proposed calibration [27] .…”
Section: Discussionmentioning
confidence: 96%
“…Measurements of SI, TIBC, and TSAT are useful for the clinical diagnosis of iron-deficiency anemia [32]. SI is the amount of circulating iron that is bound to transferrin.…”
Section: Si Tibc and Tsat Levels Of Ratsmentioning
confidence: 99%
“…We reported recently that total ironbinding capacity (TIBC) values calculated from serum iron and unsaturated iron-binding capacity (UIBC) values were significantly lower than those obtained by a direct and fully automated TIBC assay (1,2 ). We also reported that slopes of regression lines for calculated TIBC values plotted against serum transferrin (TRF) were Ïł7% lower than the theoretical ratio of TIBC to TRF (TIBC/TRF Ï­ 25.1 mol/g).…”
Section: To the Editormentioning
confidence: 99%
“…With a complete lack of both transferrin N-glycans (2,10,11 ), the structure of asialotransferrin is different from the structure(s) of the non-CDT isoforms. Thus, there is the possibility of raising a specific antibody that binds strongly to the analyte (asialotransferrin), e.g., to an epitope near or at the original point of attachment of the carbohydrate chain(s).…”
mentioning
confidence: 99%